Advanced mathematical methods in environmental and resource economics: World Scientific Lecture Notes In Economics And Policy-Vol.13 - Xepapadeas, Anastasios (New Jersey World Scientific, 2023)
The most interesting issues in environmental and resource economics have an explicit temporal dimension, since variables of interest such as pollutants, greenhouse gases, biomass of biological resources, or the stocks of fossil fuels accumulate in the ambient environment or are depleted through human actions and natural processes. The purpose of these lectures is to present the mathematical tools for analyzing environmental and resource management issues in a dynamic set-up. The lectures include a brief description of differential equations and then move on to describe methods of optimal control, dynamic programing, and differential games. The final chapters cover two novel topics: (1) environmental issues characterized by deep uncertainty, and aversion to ambiguity using robust control methods and formulations of precautionary policies; and (2) the study of pollution/resource management in space and time when the environmental variables evolve in time and diffuse in space.
Keywords: Environmental economics--mathematical models; Environmental policy--economic aspects; Natural resources--mathematical models